Factor structure of the effectiveness the teaching process in higher education institutions - Papić Blagojević, Nataša; Vukadinović, Maja; Jovičić Vuković, Ana (Ekonomija - teorija i praksa, 2022)
The present study aims at investigating the students’ perception of indicators of effectiveness of the teaching process in higher education institutions. 361 students from five different post-secondary vocational schools participated in the research. The instrument consisted of a list of indicators of the effectiveness of the teaching process, which has been taken from previous research related to characteristics of education at universities. The list included 13 indicators: knowledge, quality, creativity, flexibility, collegiality, critical thinking, cognitive skills, teamwork, cooperation, entrepreneurial spirit, interactivity, objective grading scale and the availability of teaching staff. The exploratory factor analysis was applied to extract the main components. The results have shown that the structure of the effectiveness of the teaching process from the perspective of students consists of two dimensions: Cooperation and Objectiveness.The improvement of the teaching process with the goal of its greater effectiveness is discussed in the context of these results.